2021
DOI: 10.3389/fpsyg.2021.518369
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Validity of Character Strengths as Predictors of Job Performance Beyond General Mental Ability and the Big Five

Abstract: Over the last decades, various predictors have proven relevant for job performance [e.g., general mental ability (GMA), broad personality traits, such as the Big Five]. However, prediction of job performance is far from perfect, and further potentially relevant predictors need to be investigated. Narrower personality traits, such as individuals' character strengths, have emerged as meaningfully related to different aspects of job performance. However, it is still unclear whether character strengths can explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…However, there are a couple of other studies indicating that character strengths might outperform other commonly used performance predictors, such as GMA and personality (e.g. Duckworth and Seligman 2005;Harzer et al 2021), in predicting both job and academic achievement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, there are a couple of other studies indicating that character strengths might outperform other commonly used performance predictors, such as GMA and personality (e.g. Duckworth and Seligman 2005;Harzer et al 2021), in predicting both job and academic achievement.…”
Section: Discussionmentioning
confidence: 99%
“…character strengths, grit, hardiness, selfdiscipline and self-control) can also function as important predictors of both academic achievement and job performance (e.g. Duckworth and Seligman 2005;Harzer and Ruch 2014;Harzer et al 2021;Lounsbury et al 2009). Harzer et al (2021) found, for example, that 'perseverance, teamwork and leadership seemed to be especially relevant for numerous dimensions of job performance', and that these three character strengths explained a substantial amount of variance in job performance even after controlling for GMA and personality.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…While a sizeable overlap with the personality traits of the FFM is to be expected; however, empirical studies have shown that character strengths and FFM personality traits are not redundant (McGrath et al, 2020;Noftle et al, 2011;Ruch et al, 2021). Furthermore, character strengths predict incremental validity in various work, educational, and behavioral outcomes beyond FFM personality traits (e.g., Harzer et al, 2021;Ruch et al, 2017;. At the same time, the relationship between character strengths and cognitive personality traits has not been examined thus far.…”
Section: Character Strengths and Intelligencementioning
confidence: 99%